2021
DOI: 10.1186/s12905-021-01479-y
|View full text |Cite
|
Sign up to set email alerts
|

Women’s autonomy in refusing risky sex and associated factors in Ethiopia: evidence from 2011 to 2016 EDHS data

Abstract: Background Risky sexual behavior is a major public health concern of Ethiopians. Although studying the autonomy of women in refusing risky sex is significant to take proper actions, the issue is not yet studied. Accordingly, this population-based nationwide study was aimed at assessing women’s autonomy in refusing risky sex and its associated factors in Ethiopia. Method The sample was limited to married women of 2011 (n = 8369) and 2016 (n = 8403) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 32 publications
5
11
1
Order By: Relevance
“…The autonomy of women who live in Tigray, Somali and Addis Ababa was more likely higher in health care decision making than those who live in Dire Dawa city administration respectively. Similar to this study finding, other related studies [ 8 , 15 , 18 , 27 ] found a significant difference of women's autonomy across different geographic regional states. This might be because of the contributions and commitments of regional governments in empowering women may vary from one to another.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The autonomy of women who live in Tigray, Somali and Addis Ababa was more likely higher in health care decision making than those who live in Dire Dawa city administration respectively. Similar to this study finding, other related studies [ 8 , 15 , 18 , 27 ] found a significant difference of women's autonomy across different geographic regional states. This might be because of the contributions and commitments of regional governments in empowering women may vary from one to another.…”
Section: Discussionsupporting
confidence: 91%
“…The autonomy of women who were aged 15–24 years was found a lower position (by 32.4%) than women from 35 to 49 years of age. Corresponding to this study’s finding, others studies which focused on women’s autonomy in health care decision making [ 8 , 10 , 17 , 18 , 29 ], household decision making [ 15 ], refusing risky sex [ 27 ] and on reproductive human rights [ 37 ] the age of respondents had significant effect. This might be due to the fact that “older age is associated with decreases in self-esteem” [ 38 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Figure 1 presents the three sets of explanatory variables analysed. Firstly, seven individual-level characteristics already identified as important correlates of sexual and reproductive autonomy in existing studies [ 26 , 40 , 42 44 ] were selected. These are maternal age group (15–24, 25–34, and 35 +), maternal education level (none, primary, secondary, and higher), nature of first marriage (child marriage or not child marriage), parity (primiparity, multiparity, and grand multiparity), work status (employed or unemployed), religion (Islam or Christianity), and media exposure (low, moderate, and high).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, women’s empowerment approaches that promote economic decision making, negotiation of sexual activity, or perceived agreement on fertility preferences were also related to higher contraception use in selected African countries ( Do and Kurimoto 2012 ). Women’s empowerment was also related to increase in attitudes for safer sex negotiation in several countries from South Asia and SSA, although the association vary across countries and age or other demographic characteristics ( Tenkorang 2012 ; Atteraya, Kimm, and Song 2014 ; Jesmin and Cready 2014 ; Sano et al, 2018 ; Asabu 2021 ; Putra, Dendup, and Januraga 2021 ).…”
Section: Introductionmentioning
confidence: 99%